THESIS THE APPLICATION OF VALUE CREATION IN PROMOTING SUSTAINABLE PUBLIC TRANSPORTATION (A COMPARATIVE STUDY OF TRANSJAKARTA BRT AND VÃRMLANDSTRAFIK AB) - , IBNU ROMADHONA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The concept of sustainable development requires that every attempt is development of infrastructure and physical facilities that do still maintain environmental conditions. Transportation is the biggest problem that needs to be addressed because it has a damaging effect on the environment. Influence of carbon dioxide (CO2) which comes from vehicle emissions can cause air pollution that gives a negative effect on health. The rapid growth of vehicles in big cities like Jakarta affects the urban transport system negatively. Communities are encouraged to use private cars and motorcycles in the absence of convenient public transportation, safe and timely manner. This gives the conclusion that transport needs to be monitored. Policies can be instituted to mitigate the negative consequences of this transport problem. The thesis aims to assist policy-makers and program-designers in making public transportation systems in Jakarta more sustainable by employing a value creation approach based on Service-Dominant Logic (S-D Logic). This thesis will discuss the problem of public transportation as a tool for sustainable development and value creation. The focus of this research is to review the contributions of value creation based on S-D logic in promotes the sustainable public transportation and to assess the application of value creation framework on Bus Rapid Transit (BRT) system in Jakarta, Indonesia by using public transport experience in VÃ¤rmlands, Sweden. The primary data were collected through interviewed the representatives of the related institution and for secondary data, the data were collected from official website, media news, journal, reports, etc. Then, it is analyzed by using cross-case synthesis with literature review as the consideration. The framework consists of five dimensions along value creation based on S-D Logic occurs. The dimensions include engaging customerâs emotionally in the marketing activities, offering self-service options to customers, involving customers in staging customer experiences, solving customer problems and getting customers involved in designing services. This thesis also tries to examine proposed policy recommendations to promoting public transportation as a means for environmental sustainability. The need of applying value creation framework on public transportation in Jakarta is to reducing travel trends for private vehicle, improve the current system of public transportation, encouraging use of public transport system, improving public transport market share and thus lessening global vehicle emissions.